Cystatin C, chronic kidney disease and retinopathy in adults without diabetes. (September 2016) - Ng, Wei Yan; Teo, Boon Wee; Tai, E Shyong; Sethi, Sunil; Lamoureux, Ecosse; Tien Yin, Wong; Sabanayagam, Charumathi
Background: Serum cystatin C, a novel marker of renal function has been shown to be superior to serum creatinine in predicting renal function decline and adverse outcomes of chronic kidney disease (CKD). Our aim was to investigate the association between cystatin C and retinopathy in adults without diabetes. Methods: We examined 1725 Indian adults, aged 40–80 years who participated in the Singapore Indian Eye Study (2007–2009) and were free of diabetes mellitus. CKD was defined as an estimated glomerular filtration rate (eGFR) <60 ml/min/1.73 m 2 determined from serum cystatin C (CKD-eGFRcys, n = 199), and serum creatinine (CKD-eGFRcr, n = 81). Retinopathy was assessed from digital fundus photographs of both eyes by trained graders using the modified Airlie House classification. The associations of CKD defined by the two markers alone and in combination (confirmed CKD, eGFRcr <60 and eGFRcys <60, n = 58) with retinopathy were examined using logistic regression models adjusted for potential confounding factors including preexisting cardiovascular disease and albuminuria. Results: The prevalence of retinopathy among those with CKD-eGFRcr and CKD-eGFRcys was 9.9% and 8.5%, respectively. In separate models, the associations of retinopathy with both CKD-eGFRcys (odds ratio (OR) (95% confidence interval (CI)) = 2.18 (1.14–4.16)) and CKD-eGFRcr were significant (OR (95% CI) = 2.63 (1.10–6.28)). In models including both markers, compared to optimal kidney function (eGFRcr ≥60 and eGFRcys ≥60), confirmed CKD was associated with a fourfold higher odds of retinopathy (OR (95% CI) = 4.01 (1.52–10.60)). Conclusions: In a population-based sample of Indian adults without diabetes, CKD defined by both cystatin C and creatinine was strongly associated with retinopathy.